NLRP3 activation induces BBB disruption and neutrophil infiltration via CXCR2 signaling in the mouse brain - Jaeho Lee; Wooyoung Cho; Je-Wook Yu; Young-Min Hyun (Journal of Neuroinflammation)
Abstract NLRP3 is an intracellular sensor molecule that affects neutrophil functionality and infiltration in brain disorders such as experimental autoimmune encephalomyelitis (EAE). However, the detailed molecular mechanisms underlying the role of NLRP3 in these processes remain unknown. We found that NLRP3 is crucial for neutrophil infiltration, whereas dispensable for neutrophil priming. Notably, NLRP3 activation in neutrophils induced blood-brain barrier (BBB) disruption and neutrophil infiltration into the brain via CXCL1/2 secretion and subsequent activation of the CXCL1/2-CXCR2 signaling axis. Moreover, CXCL1 and CXCL2 in the inflamed brain directly reduced Claudin-5 expression, which regulates BBB permeability in brain endothelial cells. Furthermore, neutrophil-specific NLRP3 activation aggravated EAE pathogenesis by promoting CXCR2-mediated infiltration of both neutrophils and CD4+ T cells into the central nervous system at disease onset. Thus, the CXCL1/2-CXCR2 axis plays a role in EAE progression. Therefore, this chemokine axis could be a potential therapeutic target for attenuating neuroinflammatory diseases through modulating of neutrophil and CD4+ T cell infiltration and BBB disruption.